THE IMPLEMENTATION OF INQUIRY LEARNING MODEL TO IMPROVE SELF-CONCEPT AND LEARNING ACHIEVEMENT OF THE STUDENTS OF SMA LAB UNDIKSHA - Pujani, Ni Made (Unnes Science Education Journal, 2017)
This study aim was improvement (1) students self-concept, (2) students learning achievement of physics, and (3) describe the response of students towards inquiry learning model implementation. This study was an action research conducted in two cycles. Subjects were student class XI.A2 of SMA Lab Undiksha academic year 2012/2013, which consist of 39 people. Data collected by administering tests, questionnaires and observation sheets. The data that obtained, analyzed by descriptive statistics. The results shows that (1) there are improvement in students self-concept from first cycle (M = 102.4) to second cycle (M = 113.2), medium categorized, (2) an improvement in the average value of students learning achievement from first cycle (M = 75.5) to second cycle (M = 80.5) good categorized, and (3) students responses to the implementation of inquiry learning model is positive.